The destruction of nature in the Soviet Union - Komarov, Boris, 1944- (London : Pluto Press)
Broad indictment of the environmental practices and policies of the Soviet Union.
Translation of Unichtozhenie prirody.
Includes bibliographical references and index (p. 147-149).
Keywords: Pollution -- Soviet Union; Ecology -- Soviet Union